Embracing my multiple selves. Adult education as a path of understanding - Formenti, Laura (Adult Education Discourses, 2024)
In this contribution, I track my professional path as a researcher, using some keywords to identify the main turning points. I try to show that my life – as any life – is the result of encounters, contexts, processes of which I have been part. It is also learning about stories. Growing older, and doing biographical research, I have learnt – and am still learning - to embrace the complexity of my experience, the shadows, the unaccomplished. I am grateful for the mysterious path that brought me, at a point, to do research in adult education. This kind of research is an extraordinary opportunity to become reflexive about learning, about myself as a learner, and as a human being, by answering the questions where, how, and from whom I have learnt? By talking about some stumbling stones and pilgrims I have met on my journey, I try to build a satisfying theory of life. Satisfying for me, of course. In this moment, at least.